When the End Effector Is a Laser: A Review of Robotics in Laser Surgery. (13th September 2022) - Lee, Hun Chan; Pacheco, Nicholas E.; Fichera, Loris; Russo, Sheila
Abstract : Combining laser technology with robotic precision and accuracy promises to introduce significant advances in minimally invasive surgical interventions. Lasers have already become a widespread tool in numerous surgical applications. They are proposed as a replacement for traditional tools (i.e., scalpels and electrocautery devices) to minimize surgical trauma, decrease healing times, and reduce the risk of postoperative complications. Compared to other energy sources, laser energy is wavelength‐dependent, allowing for preferential energy absorption in specific tissue types. This potentially leads to minimizing damage to healthy tissue and increasing surgical outcomes control and quality. Merging robotic control with laser techniques can help physicians achieve more accurate laser aiming and pave the way to automatic control of laser–tissue interactions in closed loop. Herein, a review of the state‐of‐the‐art robotic systems for laser surgery is presented. The goals of this paper are to present recent contributions in advanced intelligent systems for robot‐assisted laser surgery, provide readers with a better understanding of laser optics and the physics of laser–tissue interactions, discuss clinical applications of lasers in surgery, and provide guidance for future systems design. Abstract : Lasers have become a widespread tool in numerous surgical applications. Recent progress on advanced intelligent systems for robot‐assisted laser surgery is comprehensively summarized and discussed focusing on laser optics and the physics of laser–tissue interactions, clinical applications of lasers in surgery, and robotic laser steering methods. Future directions and guidance for future systems design and development are discussed.